Proper performance of duties that ensure the adversarial nature of criminal proceedings in Russia - E. N. Petukhov; M. A. Neymark (Правоприменение)
The subject of the research is the mechanism for the execution of criminal procedural duties that ensure the implementation of adversarial in Russian criminal proceedings.The subject of the research is the mechanism for the execution of criminal procedural duties that ensure the implementation of adversarial in Russian criminal proceedings. The purpose of the research is to justify the existence of the problem of organizational-legal support for the proper fulfillment of the duties assigned to participants in the criminal process and to determine the main ways of solving. The hypothesis of the research is the thesis that the combination of legal, organizational, and other means existing in criminal procedure legislation does not guarantee the proper fulfillment of the duties imposed by the legislator on the participants in adversarial criminal proceedings.of the research is to justify the existence of the problem of organizational-legal support for the proper fulfillment of the duties assigned to participants in the criminal process and to determine the main ways of solving. The hypothesis of the research is the thesis that the combination of legal, organizational, and other means existing in criminal procedure legislation does not guarantee the proper fulfillment of the duties imposed by the legislator on the participants in adversarial criminal proceedings.The methodology. General scientific dialectical methods made it possible to study the conditions and the process of evolution of legal duties, to reveal their essence in the field of criminal proceedings. The system-structural method and the situational modeling method were used when studying the intra-system relationships of elements of the mechanism for the execution of criminal procedural duties and the system of means that ensure its implementation. The study of regulatory legal requirements was carried out using the formal legal method.The main results, scope of application. The article examines the problem of organizationallegal support for the proper performance of the duties assigned to participants in the criminal process, guaranteeing the proper implementation of adversarial in criminal proceedings. The general concept of duty is given, and the definition of criminal procedure is formulated. The nature of the duties is revealed and their classification is proposed. The fundamental legal significance of the category "Adversarial" as a principle of criminal procedure is identified and the significance of criminal procedural duties as the main security means of the specified procedural category is justified. The provisions of the current criminal procedure legislation in Russia are critically analyzed from the point of view of the presence or absence of legal and organizational means in them that ensure the creation of the conditions necessary for the emergence of a real possibility of proper performance of duties by participants in the criminal process. It is established that the organizational and legal resources required to effectively ensure the proper performance of criminal procedural duties are insufficient. A problematic situation in criminal proceedings is revealed in the form of imperfection of the means intended to achieve his appointment in the context of the implementation of the adversarial legal regime. The views of scientists on the issues studied in the article are studied, analyzed and evaluated.Conclusions. The essence of the scientific problem of research is formulated and proposals are put forward aimed at improving the criminal procedure regulation of the proper behavior of legally liable participants in the criminal process in order to increase the effectiveness of ensuring the implementation of adversarial in criminal proceedings in Russia.